Women, welfare and productivism in East Asia and Europe - Chau, Ruby C. M.; Yu, Sam W. K. (Research in comparative & global social policy., 2022)
Developing the new framework of 'life-mix', which considers the mixed patterns of caring and working in different periods of life, this book systematically explores the interplay of productivism, women, care and work in East Asia and Europe. The book ranges across four key aspects of welfare -- childcare, parental leave, employment support and pensions -- to illustrate how policies affect women in various periods of their lives. Policy case studies from France, Germany, Hong Kong, Hungary, South Korea, Sweden and the UK, show how welfare could support people's caring and working lives. This book forms a prescient examination of how productivist thinking underpins regimes and impacts women's welfare, care and work in both the East and West.